Repercussions of the pandemic on tuberculosis control actions from the perspective of health professionals - Sabrina da Silva de Souza; Roxana Isabel Cardozo Gonzales; Hellen Cristina Sthal; Daiane Cardoso da Silva; Marcela Flavia Lopes Barbosa; Tatiana Conceição (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to analyze the repercussions of the COVID-19 pandemic on tuberculosis control actions from the perspective of primary health care professionals. Methods: this descriptive study with a qualitative approach was conducted from November 2022 to April 2023, using semi-structured interviews with 11 key informant professionals from primary health care units in a Brazilian capital. Data were organized using Atlas.ti 22.0 software and subjected to thematic-categorical content analysis. Results: the pandemic scenario caused alterations in the work process, necessitating abrupt adaptations, and led to detrimental impacts on the health of professionals and tuberculosis control actions, which were reduced or discontinued. Final Considerations: there was evident unpreparedness and a lack of resources from various governmental levels and health services to handle the public health emergency situation without severe harm to the provision of essential services.